Carboniferous high-Mg andesitic and dioritic rocks in the Aqishan-Yamansu belt: Implications for mantle metasomatism and tectonic setting of the Eastern Tianshan. (1st October 2021) - Zhao, Liandang; Chen, Huayong; Han, Jinsheng; Zhang, Shuanliang
Graphical abstract: Highlights: Early Carboniferous high-Mg andesitic tuff and diorite were discovered in the Aqishan-Yamansu belt. The high-Mg rocks were formed by interaction of sediment-derived melts and the depleted mantle wedge. The Aqishan-Yamansu belt was a continental arc-related basin in the Carboniferous. The sharp changes of geochemical features in the Aqishan-Yamansu belt indicate an important tectonic transition. Abstract: The Aqishan-Yamansu belt, Eastern Tianshan is characterized by voluminous Late Paleozoic intermediate–felsic igneous rocks and magmatic–hydrothermal Fe (–Cu) deposits. This study presents zircon U–Pb ages and whole-rock geochemistry of newly identified high-Mg andesitic and dioritic rocks (HMAs and HMDs) within the Hongshanliang copper district in the Aqishan-Yamansu belt, Eastern Tianshan to investigate their petrogenesis and constrain the Carboniferous tectonic setting of the Eastern Tianshan. Zircon U–Pb dating of the HMAs and HMDs yielded ages between 336.9 ± 1.9 Ma and 329.0 ± 4.2 Ma. The HMAs and HMDs show calc-alkaline affinities, and exhibit weak Rb, Ba, U, and Pb enrichment and Nb and Ta depletion, with minor negative Eu anomalies. Moreover, the positive εNd (t) values (+6.4 to +6.6), low Th and (La/Sm)N contents/ratios, as well as relatively low and variable εHf (t) values (−3.71 to +1.55) indicate that they were probably sourced from a depleted mantle wedge with negligible to minor crustal contamination. They have low Ba/Th ratios (10.8–93.3), minor negative Eu anomalies, high and variable (La/Sm)N and Th/Yb ratios, which are comparable to the well-known sanukites of the Setouchi volcanic belt, suggesting involvement of sediment-derived magmas during their formation. Integrating published regional mafic–intermediate rocks from the Aqishan-Yamansu belt and this study, we propose that the Hongshanliang high-Mg rocks formed in a continental arc-related setting in the Carboniferous and the belt underwent a sharp tectonic transition event (ca. 330–322 Ma) from the Kangguer oceanic slab steepening to breakoff, corresponding to the Late Carboniferous basin inversion.